A multicenter, phase 1, dose escalation clinical trial (G-FORCE-1) of XRT, RRx-001 and temozolomide followed by temozolomide +/- RRx-001 in newly diagnosed glioblastoma - Fine, Howard; Reid, Tony; Caroen, Scott; Oronsky, Bryan; Abrouk, Nacer; Butowski, Nicholas (Frontiers in Oncology, 2023)
The current standard of care for newly diagnosed glioblastoma (GBM) is maximum surgical resection followed by concurrent treatment with temozolomide (TMZ) and radiotherapy (RT) and then six to twelve cycles of maintenance TMZ. RRx-001, an NLRP3 inhibitor and nitric oxide (NO) donor with chemoradiosensitizing, vascular normalizing and macrophage repolarizing properties, is currently in a Phase III trial for small cell lung cancer (SCLC). The purpose of this non-randomized trial was to establish the safety and look for a signal of clinical activity of RRx-001 as an add-on to RT and TMZ in patients with newly diagnosed glioblastoma.